Thoracic endovascular aortic repair and coil embolization of the pulmonary artery for primary racemose hemangioma of the bronchial artery with a bronchial-pulmonary artery fistula. (August 2015) - Matsubara, Yutaka; Morisaki, Koichi; Matsuda, Daisuke; Aoyagi, Yukihiko; Tanaka, Shinichi; Okadome, Jun; Fukunaga, Ryota; Matsumoto, Takuya; Maehara, Yoshihiko
A 69-year-old male visited a doctor with dyspnea. A bronchial-pulmonary artery fistula, which is called racemose hemangioma, and dilated pulmonary artery were detected by a computed tomography (CT) scan. The bronchial-pulmonary artery fistula can cause lethal hemoptysis, therefore, we performed thoracic endovascular aortic repair (TEVAR) to seal the bronchial artery and coil embolization of the pulmonary artery. Postoperative CT showed the thrombosed racemose hemangioma of the bronchial artery. TEVAR and coil embolization of the pulmonary artery is considered to be a useful treatment option for a racemose hemangioma.